2020
DOI: 10.1101/2020.12.04.20244137
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting Hospital Utilization and Inpatient Mortality of Patients Tested for COVID-19

Abstract: Using structured elements from Electronic Health Records (EHR), we seek to: i) build predictive models to stratify patients tested for COVID-19 by their likelihood for hospitalization, ICU admission, mechanical ventilation and inpatient mortality, and ii) identify the most important EHR-based features driving the predictions. We leveraged EHR data from the Duke University Health System tested for COVID-19 or hospitalized between March 11, 2020 and August 24, 2020, to build models to predict hospital admissions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…For instance, Mu 17 discussed how constraints on inter-city travel (reaching a 70% reduction in people flow) in China slowed the spread of COVID-19 cases throughout the country. Furthermore, as we did in the present work, Davis et al 16 employed a complex network model based on human mobility to inspect the domestic seeding of COVID-19 cases within the USA. Their analysis revealed that, even though international travel was a key driver to the initial disease spread in certain metropolitan areas, many states were infected by domestic travel flows.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Mu 17 discussed how constraints on inter-city travel (reaching a 70% reduction in people flow) in China slowed the spread of COVID-19 cases throughout the country. Furthermore, as we did in the present work, Davis et al 16 employed a complex network model based on human mobility to inspect the domestic seeding of COVID-19 cases within the USA. Their analysis revealed that, even though international travel was a key driver to the initial disease spread in certain metropolitan areas, many states were infected by domestic travel flows.…”
Section: Discussionmentioning
confidence: 99%
“…Severe COVID-19 patients have higher serum complement protein C5a level than mild patients and healthy people. The CoVs’ nuclear proteins bind to mannan-binding lectin serine protease 2 (MASP-2), a key protein of the LP activation, resulting and aggravating inflammatory lung injury [ 79 , 80 ]. In addition, C5b-9, C4d and MASP-2 deposits were found in the microvasculature of lung and skin biopsy in severe COVID-19 patients, consistent with activation of the AP and LP of complement [ 81 ].…”
Section: Complement As a Target Of Inhibiting Cytokine Storm In Covid-19mentioning
confidence: 99%
“…Indeed, elevated plasma C5a levels in COVID-19 patients are consistent with the clear role of C5a in promoting lung sequestration of leukocytes and pulmonary dysfunction, that reflects the severity of the disease. It also indicates that sC5b-9 has similar effects, which can cause leukocyte migration across the epithelium and vascular leakage [ 80 , 106 ].…”
Section: Complement As a Target Of Inhibiting Cytokine Storm In Covid-19mentioning
confidence: 99%
“…Connor et al 47 proposed models to predict hospitalization within 4 weeks of an outpatient COVID-19 test, ICU admission, mechanical ventilation and inpatient mortality by leveraging EHR data from the Duke University Health. For each type of models, three classifiers were considered including logistic regression, XGBoost and LGBM.…”
Section: Related Workmentioning
confidence: 99%